2021
DOI: 10.1093/annweh/wxaa142
|View full text |Cite
|
Sign up to set email alerts
|

Are Inflammatory Markers an Indicator of Exposure or Effect in Firefighters Fighting a Devastating Wildfire? Follow-up of a Cohort in Alberta, Canada

Abstract: Objectives The Fort McMurray fire in Alberta, Canada, devastated the townsite in May 2016. First responders were heavily exposed to smoke particles. Blood samples taken from firefighters in May and August/September 2016 were used to measure concentrations of inflammatory markers in plasma and the relation of these markers to exposures and respiratory ill-health. Methods Blood samples were drawn from firefighters from two fire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
0
5
0
1
Order By: Relevance
“…Although the main aim of the study was to help identify approaches to the primary prevention of harm to firefighters, a secondary goal was to use the data to assist in determining whether damage to firefighters' health was indeed fire-related. In one paper ( 8 ) we examined the relation of inflammatory markers, taken 3–4 months after the start of the fire, to both exposure and respiratory ill-health and suggested that, in the absence of external estimates of exposure, long term biomarkers might be a useful proxy. From the clinical assessment of those with ongoing respiratory problems, we suggest that the combination of airways hyperreactivity and bronchial wall thickening might be used as a marker of fire-related damage ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the main aim of the study was to help identify approaches to the primary prevention of harm to firefighters, a secondary goal was to use the data to assist in determining whether damage to firefighters' health was indeed fire-related. In one paper ( 8 ) we examined the relation of inflammatory markers, taken 3–4 months after the start of the fire, to both exposure and respiratory ill-health and suggested that, in the absence of external estimates of exposure, long term biomarkers might be a useful proxy. From the clinical assessment of those with ongoing respiratory problems, we suggest that the combination of airways hyperreactivity and bronchial wall thickening might be used as a marker of fire-related damage ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…At the second follow-up participants also completed the ECHRS. Using the approach of Sunyer et al ( 18 ) we had extracted 4 factors ( 8 , 12 ) we labelled as reflecting cough, phlegm, asthma and wheeze. We also asked if they had any ongoing lung or breathing problems related to the fire.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tulekov, L.A. Strizhakov, S.A. Babanov, N.E. Lavrentyeva SPIROMETRy AND RESPIRATORy DISEASE RISk FACTORS IN FIREFIghTERS IN ALMATy Оccupational medicine 3.2.4 Введение Профессия пожарного предполагает, что вероятность контакта с вредными факторами остаётся высокой, даже несмотря на использование современных средств защиты органов дыхания [1]. В мировой литературе опубликовано большое количество исследований о влиянии профессиональных вредностей на рабочем месте пожарного на показатели функции внешнего дыхания и риск развития отдельных болезней органов дыхания [2,3], а также отдельные гигиенические исследования концентрация вредных загрязнителей в воздухе [4][5][6][7][8].…”
unclassified